Dinâmica socioespacial do centro de fortaleza com base nos serviços educacionais - Holanda, Júlia Monteiro (2016)
The city is the realization of social agents in space. It is understood that it is the spatialized history of society. The movement of production and organization of urban space, innovations are based in the city, the result of immediate demands and brief of the capitalist mode of production. So the city centers become dynamic, where there are intense and rapid change. Having said that, the center of Fortaleza should be understood inserted in the urban restructuring of Fortaleza, since it has undergone significant changes that redefined completely within the frame of present relations in the city. It is noted that the tertiary sector of the economy increasingly is reaching new areas and thus directly interfering with production and socio-spatial organization. In this context, there is the expansion of educational services as one of the key attributes that enhance intraand inter-relationships and stimulates the economy. Thus faces, this research aims to understand the dynamics of Fortaleza Center based on educational services present in the neighborhood. To achieve the proposed goal, this work was based on the by the following methodological approach: literature search based on relevant references to research, fieldwork, data collection and interpretation of public agencies data (PMF, SDE, INEP, SECITECE, EEC, IBGE), questionnaires and building tables, charts and graphs. The results of this work indicate that the Center of Fortaleza attracts fixed and flows destined to educational services, demonstrating the conjunctural current situation of the neighborhood, as a centrality focused on meeting the demands of popular segments of society.Thus, the work helps in understanding the socio-spatial dynamics of the Fortaleza center, and may serve as the basis for future research on themes addressed and possibly in the implementation of public policies aimed at urban planning.